Working with Commercially Available Quantum Dots for Immunofluorescence on Tissue Sections. - Sandrine Prost; Ria E B Kishen; David C Kluth; Christopher O C Bellamy (PLoS ONE)
Quantum dots are semiconductor fluorescent nanocrystals that exhibit excellent characteristics compared with more commonly used organic fluorescent dyes. For many years quantum dot conjugated products have been available in multiple forms for fluorescence imaging of tissue sections under the trademark name Qdot®. They have much increased brightness, narrow emission spectrum, large Stokes shift and photostability compared with conventional organic fluorescent dyes, which together make them the fluorophores of choice for demanding requirements. Vivid Qdots are recent replacements for original Qdots, modified to improve brightness, however this has affected the fluorescence stability in commonly used conditions for immunohistochemistry. We present here our investigation of the stability of original and Vivid Qdots in solution and in immunohistochemistry, highlight the potential pitfalls and propose a protocol for stable and reliable multiplex staining with current commercially available original and Vivid Qdots.